Polymerization of optically active disubstituted acetylene monomers by Pd catalyst bearing bulky phosphine ligand. Issue 18 (21st March 2017) - Goto, Yuta; Miyagi, Yu; Sano, Natsuhiro; Sanda, Fumio
ABSTRACT: Chloro‐ and aryl‐substituted acetylene monomers having an optically active group were polymerized by a Pd catalyst [( t Bu3 P)PdMeCl] bearing a bulky phosphine ligand, and by MoCl5 for comparison. The corresponding disubstituted acetylene polymers with M n 's = 2000–19, 500 and 6900–10, 800 were obtained in 29–83% and 11–62% yields when the Pd and Mo catalysts were used, respectively. The formation of polyacetylenes, poly[( R )‐1 p ], poly[( R )‐1 m ], and poly[( S )‐2 p ] were confirmed by SEC and the presence of a Raman scattering peak based on the alternating double bonds of the main chain. Pd‐based poly[( R )‐1 m ] exhibited CD signals around 350 nm assignable to a certain secondary structure, while Mo‐based poly[( R )‐1 m ] did not. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 3011–3016 Abstract : Chloro‐ and aryl‐substituted acetylene monomers having an optically active group were polymerized by [( t Bu3 P)PdMeCl] as a catalyst to obtain the corresponding disubstituted acetylene polymers with M n 's of 2000–19, 500 in 29–83%. The polymer having meta‐substituted phenyl groups exhibited CD signals assignable to a certain secondary structure and liquid crystalline properties.